Nature’s gift to improve soil fertility - Vakeesan, A.; Nishanthan, T.; Mikunthan, G. (LEISA Magazine, 2008)
Excessive use of inorganic fertilizers and pesticides has affected soil and water quality in the Jaffna peninsula, Sri Lanka. Students from the Faculty of Agriculture at the University of Jaffna have been learning about green manures from farmers, and how they have been used to improve soils. Green manures were also used successfully to rehabilitate salinated soils affected by the tsunami. These and other organic practices are now being promoted with and by farmers